Pengembangan Instrumen Angket Faktor-Faktor Penyebab Kesulitan Belajar Siswa pada Materi Larutan Penyangga Kelas XI Fase F SMA - Nur Bayang Matogu; Bali Yana Fitri (MASALIQ, 2026)
Difficulties in learning chemistry remain a common problem among students because chemistry learning requires not only conceptual mastery but also the ability to connect macroscopic, microscopic, and symbolic representations. These difficulties may be influenced by students’ internal factors as well as external factors related to the learning environment; therefore, a valid instrument is required to accurately identify their contributing factors. This study aimed to develop a valid questionnaire instrument for identifying the factors causing students’ learning difficulties in the topic of buffer solutions. The study employed a research and development method by adapting DeVellis’s scale development stages, which included determining the construct, developing statement items, determining the measurement format, expert validation, and instrument revision. The content validity of the instrument was assessed by five expert lecturers using Aiken’s V index. The results showed that the instrument obtained a mean Aiken’s V value of 0.91 and was classified as valid. Thus, the developed questionnaire instrument met the content validity criteria and can be used to identify the factors causing students’ learning difficulties in the topic of buffer solutions. This instrument contributes by providing an identification tool that can support teachers and researchers in systematically mapping the factors associated with difficulties in learning chemistry as a basis for planning instruction that meets students’ needs.